Effect of Hydrolysis time and Papain Concentration on Some Properties of Apple Snail (Pilla ampullacea) Hydrolysate - Andre Yusuf Trisna Putra; Dedin Finatsiyatull Rosida; Anugerah Dany Priyanto (Engineering Faculty, University of Pembangunan Nasional Jawa Timur, 2020)
content and total peptide content were investigated in the non-farmed freshwater apple snail (Pila ampullacea) to understand its nutritional potential as alternative umami taste enhancer. Apple Snail samples with removed gut content were collected from a local snail non-farm in Surabaya City. Papain enzyme was used. The two variables, hydrolysis time (3, 6, 9, 12, 15, 18 h) and enzyme concentration (1%, 5%, 10%), was used to produce the apple snail hydrolysate. The result showed that total soluble protein was about 2.1%-7.3%, whereas total peptide content was 5.05-15.73mg/ml. The highest total soluble protein was achieved at 12 hour. Longer hydrolysis time significantly effect on total peptide content of apple snail hydrolysate.